Pengaruh Pemberian Kombinasi Madu dan Habbatussauda Terhadap Fungsi dan Fibrosis Ginjal Tikus - Kamilia Dwi Utami; Ulfah Dian Indrayani; Israhnanto Isradji; Hanifah Tiara Putri; Hilwa Qonita Almazia; Yusri Apriliani Karyono (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Honey has ingredients that can provide antioxidant effects, while Black Seed contains thymoquinone which has antioxidant, anti-inflammatory and anti-microbial effects. This study aims to determine the effect of giving a combination of honey and Black Seed on urea levels in rats induced by Unilateral Ureteral Obstruction (UUO). This study used a pretest-posttest randomized controlled group design for urea and creatinine and a posttest only controlled group design for the percentage fraction of areas of renal fibrosis. The test subjects were 30 Rattus Wistar male white rats randomized into 5 groups namely group 1 (Sham Operation), group 2 (irbesartan 13.5 mg/kgBW/day), group 3 (combination of honey 0.675 mL/200 g/day and Black Seed 0.5 mL/kgBW), group 4 (combination of honey 1.35 mL/200 g/day and Black Seed 1.0 mL/kgBW), and group 5 (combination of honey 2.025 mL/200 g/day and Black Seed 2.0 mL/kgBW). Urea levels were examined using enzymatic methods. Analysis of urea levels pretest-posttest using One Way Anova followed by Post Hoc test. The results of measuring urea levels in the pretest showed an increase in urea levels in all UUO-induced groups, while measurements of urea levels in the posttest showed a decrease in urea levels compared to the pretest. Analysis of creatinine levels pretest using One Way Anova followed by Post Hoc test while posttest analysis using Kruskal Wallis followed by Mann Whitney test. The results of measuring creatinine levels in the pretest showed an increase in creatinine levels in all UUO-induced groups, while measurements of creatinine levels in the posttest showed a decrease in creatinine levels compared to the pre test. The percentage of kidney fibrosis area fraction in groups 1, 2, 3, 4, and 5 were as follows: 0%, 2%, 7%, 5.5%, and 1.5%, respectively. Analysis of the results of the area fraction of renal fibrosis using Kruskal Wallis followed by the Mann Whitney test. The results of measuring the area fraction of fibrosis showed a decrease in the percentage of area fraction in the test group. Administration of a combination of honey reduced urea and creatinine levels and the percentage of fibrous area fraction of rats induced by unilateral ureteral obstruction.Keywords: Unilateral Ureteral Obstruction; honey; Black Seed; urea; creatinine; area fraction; kidney fibrosisABSTRAK Madu memiliki kandungan yang dapat memberikan efek antioksidan, sedangkan habbatussauda mengandung thymoquinone yang memiliki efek antioksidan, anti inflamasi, dan anti mikroba. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian kombinasi madu dan habbatussauda terhadap kadar ureum pada tikus yang di induksi Unilateral Ureter Obstruction (UUO). Penelitian ini menggunakan rancangan pretest-posttest randomized controlled group untuk ureum dan kreatinin serta posttest only controlled group design untuk persentase fraksi area fibrosis ginjal. Subjek uji adalah 30 ekor tikus putih jantan Rattus Wistar dirandomisasi menjadi 5 kelompok yaitu kelompok 1 (Sham Operation), kelompok 2 (irbesartan 13,5 mg/kgBB/hari), kelompok 3 (kombinasi madu 0,675 mL/200 g/hari dan habbatussauda 0,5 mL/KgBB), kelompok 4 (kombinasi madu 1,35 mL/200 g/hari dan habbatussauda 1,0 mL/KgBB), dan kelompok 5 (kombinasi madu 2,025 mL/200 g/hari dan habbatussauda 2,0 mL/KgBB). Kadar ureum diperiksa dengan menggunakan metode enzimatik. Analisis kadar ureum pretest-posttest menggunakan One Way Anova dilanjutkan uji Post Hoc. Hasil pengukuran kadar ureum pretest menunjukkan peningkatan kadar ureum pada semua kelompok yang diinduksi UUO, sedangkan pengukuran kadar ureum posttest menunjukkan penurunan kadar ureum dibandingkan pretest. Analisis kadar kreatinin pretest menggunakan One Way Anova dilanjutkan uji Post Hoc sementara analisis posttest menggunakan Kruskal Wallis dilanjutkan uji Mann Whitney. Hasil pengukuran kadar kreatinin pretest menunjukkan peningkatan kadar kreatinin pada semua kelompok yang diinduksi UUO, sedangkan pengukuran kadar kreatinin posttest menunjukkan penurunan kadar kreatinin dibandingkan pre test. Persentase fraksi area fibrosis ginjal pada kelompok 1, 2, 3, 4, dan 5 masing-masing sebagai berikut: 0%, 2%, 7%, 5,5%, dan 1,5%. Analisis hasil fraksi area fibrosis ginjal menggunakan Kruskal Wallis dilanjutkan uji Mann Whitney. Hasil pengukuran fraksi area fibrosis terdapat penurunan persentase fraksi area pada kelompok uji. Pemberian kombinasi madu menurunkan kadar ureum dan kreatinin serta persentase fraksi area fibrosis tikus yang diinduksi obstruksi ureter unilateral.Kata kunci: Unilateral Ureter Obstruction; madu; habbatussauda; urea; kreatinin; fraksi area; fibrosis ginjal